Expert opinion on clinical presentation, diagnosis, and treatment of infantile-onset Pompe disease: a Delphi study in Türkiye - Ozsaydi Aktasoglu, Ekin; Inci, Asli; Oktem, Ridvan Murat; Biberoglu, Gursel; Okur, Ilyas; Ezgu, Fatih Suheyl; Tumer, Leyla (Tubitak Scientific & Technological Research Council Turkey, 2025)
Background/aim: Pompe disease (acid maltase deficiency, glycogen storage disease type II, OMIM #606800) is an autosomal recessive disorder characterized by lysosomal acid-alpha-glucosidase deficiency. The infantile-onset type of the disease is mainly characterized by cardiomegaly, hypotonia, and a high mortality rate. This study aimed to create a national consensus about infantile-onset Pompe disease (IOPD) to raise awareness among clinicians and standardize diagnosis and treatment approaches in T & uuml;rkiye. Materials and methods: The Gazi University Division of Metabolic Diseases and Nutrition developed this expert opinion consensus and expanded it to include metabolism specialists across T & uuml;rkiye. A systematic literature review was performed, and the Delphi method was used to evaluate the results. Results: Seventeen conclusive questions were produced about clinical presentation, diagnosis, and treatment, and 14 reached a consensus. Consensus was reached that general hypotonia is one of the most important findings, and agreement was also achieved on the starting dose of treatment for presymptomatic patients. The contributors agreed that gene therapy is a good treatment option for IOPD in the future. Conclusion: The topics related to this consensus will help physicians in T & uuml;rkiye and elsewhere with high incidence rates of IOPD, especially regarding diagnosis and treatment decisions.
Keywords: Acid maltase deficiency; Delphi study; expert opinion; infantile-onset Pompe disease; Turkish consensus